E-Skill dan E-Leadership: Faktor Penting dalam Meningkatkan Kinerja Pegawai di Perguruan Tinggi pada Era Digital - Febri Yoga Sapta Raharjo; Faiz Irsyad Prasetyo (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This study will analyze the influence of digital competence (E-Skills) as an important factor in improving the performance of educational staff through the moderating role of digital leadership or E-Leadership. This research uses the Structural Equation Modeling (SEM) method based on Partial Least Square which involves 120 respondents who work as Education Personnel at Pancasakti University Tegal as research samples using a questionnaire with a Likert scale of 1-5. Data analysis was processed using the SmartPLS v.4 program using the Second Order method approach. The research results show that 1) digital competence has a positive influence on the performance of educational staff, 2) The role of E-Leadership in moderating the influence of digital competence on employee performance is not statistically significant in this research. This is caused by variability in the application of E-Leadership, varying levels of digital competence among employees, as well as other contextual factors outside of the more dominant research. 3) The level of respondents' perception of Access, Use, Communication and Creation as dimensions of Digital Competence is in the medium category so efforts need to be made to increase it through developing digital competence.